Current knowledge of South American cladoceran diapause: a brief review. - Iglesias, Carlos (2016)
The study of the structure and dynamics of cladoceran egg banks in SouthAmerica began only 15 years ago and the amount of knowledge, in addition to being scarce, is widely spread over partially national journals, theses, and books, and thus partially unavailable. We conducted a review of the literature published for this region, focusing mainly on the methodological approaches that have been applied and describe the main findings already published. The different methodological approaches make data comparability difficult. However, a total of 77 egg morphotypes were identified in the published studies. Among the variety of methods used, we suggest to adopt as the standard procedure: 1) pre isolation of eggs fromthe sediments by the “Sugar Flotation Method;'' 2) identification, enumeration, and sorting of egg morphotypes present in the sample; 3) individual hatching of each egg morphotype; 4) adult individual identification to the species level according to available keys; and 5) linking identified eggs to identified species’ adults.The absence of identification keys constitutesa challenge.Therefore, collaborative research with the aim of generating pictorial taxonomical support for Neotropical resting eggs are encouraged.Webelieve the adoption of the suggested protocol might facilitate this issue. An extremely low hatching success was reported for most studies and the factors triggering the break of dormancy in the resting eggs coming from permanent systems remain unknown. In conclusion, resting egg studies are a novel and promising field in South America, but with many challenges that need to be addressed.